Designing Open Data Mobile Prototype as a Tool to enhance Transparency in Dhi-Qar: Investment Commission as a Case Study - Azeez, Hayder Hussein; Abdulhussien, Wijdan R. (University of Thi-Qar Journal, 2019)
Based on the recent statistic released by Transparency International (TI), Iraq, as a developing country, is on top of the list among the most corrupt countries. Moreover, the current government in Iraq faced an incredibly complex challenge with the collapse of the oil price and penetration of corruption in the public sector. The government is no longer able to resist the corruption that has spread significantly between government agencies. The corruption undermines the fairness and stability and also influences the services provided by the government. These issues caused by corruption may lead to the malformation of the image ofa new government. In order to solve these issues, the government entities should open their doors for the citizens. Harnessing open data in the government institutions aims to fight corruption and to strengthen governance. The availability of information would help reduce corruption by increasing transparency within the public sector. Many studies have found that Information and communication technology (ICT) represents a new way to process and disseminate information and has a positive impact on the performance of governments, in terms of either governance or efficiency.Thus, the main objective of this study is to harness themodern technologiesto designa system prototype as a platform for disseminating the latest information related to the agencies’ services and allocated budget for each project. More specifically, the investment commission is the basis of the study. In particular,this study exploited the modern platform from Google “Android studio 2.0” as the integrated development environment and Java programing to design and implement the current prototype.